Lactobacillus plantarum helps to suppress body weight gain, improve serum lipid profile and ameliorate low-grade inflammation in mice administered with glycerol monolaurate. (February 2019) - Li, Yang; Liu, Tongjie; Zhang, Xi; Zhao, Minjie; Zhang, Hui; Feng, Fengqin
Graphical abstract: Highlights: Intake of GML induced adverse effects on body weight, serum lipids and gut microbiota. L. plantarum ZJUFT17 could attenuate the adverse effects induced by GML in mice. Administration of L. plantarum ZJUFT17 could modulate the gut microbiota in mice. L. plantarum ZJUFT17 may be a candidate for probiotics. Abstract: Glycerol monolaurate (GML) is a naturally occurring surfactant and is widely used as a food emulsifier. New evidence, however, has shown that intake of GML could result in metabolic syndrome as well as gut microbiota dysbiosis in mice. In this study, male C57BL/6J mice fed normal chow diet with or without GML supplementation were administered with Lactobacillus plantarum strains isolated from Chinese sourdough for 6 weeks to investigate the influence of GML and the L. plantarum strains on body weight, serum lipid profiles, inflammatory responses and gut microbiota. The results showed that L. plantarum could attenuate the adverse effects induced by GML, especially the strain L. plantarum ZJUFT17, which showed good performance in suppressing body weight gain, lowering total cholesterol, reducing the serum tumor necrosis factor (TNF)-α level and enhancing the α-diversity of gut microbiota in mice supplemented with GML.